Exercise improves high-fat diet-induced obesity and related cardiac dysfunction in Drosophila by regulating Dilp6 through FOXO in adipose tissue. - Pan, Z.; Ding, M.; Gu, W.; Yu, Z.; Yi, Q.; Dai, J.; Wang, L.; Peng, Y.; Zhang, Z.; Zheng, L. (Life Sciences, 2026)
Obesity is a common metabolic disease, and the development of obesity can lead to related cardiovascular diseases. Therefore, this article explores the relationship between exercise and Dilp6 in lipid metabolism and the resulting cardiac function damage, as well as the role of FOXO in the relationship between exercise and Dilp6. Our results show that adipose tissue-specific knockdown of Dilp6 leads to lipid accumulation, impaired cardiac function, and reduced exercise capacity in Drosophila. Exercise can regulate Dilp6 through FOXO, improving lipid accumulation and related cardiac function damage caused by Dilp6 downregulation. Therefore, our study provides a new theoretical basis for exercise to improve obesity and obesity-induced cardiac function damage.